SOFT POWER OF THE EUROPEAN UNION: A FOCUS GROUP STUDY ON THE INFLUENCE OF FUNDAMENTAL VALUES IN TURKEY - Aydemir, Emrah (My University, 2018)
The European Union is showing an approach that shapes itsrelations on the basis of democracy and attaches importance todemocratization. The soft power of the European Union is increasing dayby day, in an effort to spread values such as human dignity, freedom,democracy, equality and rule of law. The increasing soft power of theEuropean Union has accelerated the democratic transition process inEurope and cooperative relations with the developing countries haveguided Turkey, which is an EU candidate country, and other countriesthat the Union is in contact. The magnetic attraction of the EuropeanUnion, which accelerates the transition period, causes countries to makeefforts to become a member state of the European Union. The potentialof the soft power of the European Union encourages the fundamentalvalues outside the Union and the soft power of the Union emerges as asocial influence of an international organization. In this context, theimpact of enlargement of the European Union has reveal itself in Turkeyand Turkey has made progress in the process of accession to the Unionwithin the areas of democratization and human rights. However, thefundamental values of the European Union, which constitute theattraction sources of the Union, is a matter of debate in Turkey today.With reference to this information, it has been researched whether thefundamental values of the European Union influence the perspectivetowards Union in a positive way, and whether the Union's use offundamental rights and freedoms increased the trust in the EuropeanUnion. Focus group discussion has been used as a method in the study.Three focus group discussions have been conducted and each sessionhave lasted 120 minutes. In the analysis of the result of the research,evaluations of the participants regarding to the fundamental values havebeen analyzed.
Keywords: Siyasi Bilimler; Uluslararası İlişkiler